Potret Penerapan Pendidikan Karakter di Aceh: Studi Penguatan Nilai Kearifan Lokal di Era Globalisasi - Muhammad Habibi MZ; Laitani Fauzani; Khalid Muddatstsir; Yusrizal (Institut Agama Islam Hidayatullah Batam, 2025)
Character education based on local wisdom in Aceh is the focus of this research as a response to the challenges of moral degradation and identity crisis in the era of globalization. This study aims to analyze the implementation of character education based on local wisdom in Aceh, identify factors influencing the effectiveness of integrating traditional and modern values, and explore the potential of Aceh's character education model for a global context. The research method used is a literature review with content analysis of selected scholarly works. The results show that character education in Aceh successfully integrates local and Islamic values through a holistic approach, involving educational institutions, government policies, and community participation. However, challenges such as the influence of globalization and the lack of public understanding of local wisdom still need to be addressed. These findings affirm that Aceh's character education model has the potential to serve as a model for global education systems, particularly in facing contemporary educational challenges. Recommendations for further research include quantitative studies, comparative studies, and exploration of the role of information technology in character education.